Effects of copper stress on biofilm and capsule gene expression of Streptococcus agalactiae isolated from bovine mastitis - Bonsaglia, E. C. R; Quesille-Villalobos, A. M; Rall, V. L. M [UNESP]; Pantoja, J. C. F [UNESP]; Silva, N. C. C; Santos, M. V; Reyes-Jara, Angelica (Springer Nature, 2025)
Streptococcus agalactiae biofilms challenge dairy farms by harming animal health and milk quality. Copper shows antimicrobial activity against mastitis pathogens, but its effect on S. agalactiae is unclear. This study aimed to evaluate the impact of copper on S. agalactiae isolates from cows with mastitis, evaluating its effects across multiple aspects of bacterial behavior and transcriptional responses. The 29 isolates were characterized, revealing predominantly capsular type Ia (62%) and III (38%). All isolates formed biofilms, classified as strong (59%), moderate (34%), or weak (7%) producers. The minimal inhibitory concentration (MIC) of copper was determined to be 4 mM for all isolates. Copper reduced planktonic growth, primarily affecting the maximal growth potential, while generation time and growth rate remained largely unchanged. Biofilm formation was significantly reduced in two of three selected isolates, while one isolate remained unaffected. Copper surfaces (99.9%) exhibited a bactericidal effect, producing a 3-log reduction in bacterial load within 50 min, independent of biofilm-forming capacity. Copper exposure induced expression of copY and copA genes in all three isolates, and capIa expression increased in one isolate. These findings provide novel evidence that copper can inhibit S. agalactiae growth and biofilm formation, highlighting its potential as an alternative strategy for controlling this pathogen in dairy farms.